MANAGING SOCIAL MEDIA PLATFORMS FOR BROADCASTING: USES, PROSPECTS & CHALLENGES - OLUWABUSAYO O. OLUGBAMI; PATRICIA U. SONI-ODOH; RIDWAANAH OLAJIDE (International Studies Journal, 2025)
Broadcasting has been around for over a century, and it has evolved with technology which continues to shape broadcast growth worldwide. One factor technology has introduced is the rise of social media platforms. Social media platforms have become a form of communication since their introduction, and traditional broadcasters have had to leverage them to remain relevant and reach their intended audience. This study adopted the qualitative research methodology with a semi-structured interview approach of participants from the social media and news department of NTA International, Abuja. In the course of this study, broadcasters were found to use social media both for gathering and disseminating information. Obstacles such as cyberbullying, dissemination of fake news, and citizen journalism are also faced in the field, and they are not easy to counter and require careful consideration. This study, unlike previous research that focuses solely on the benefits of digital platforms, explores the two sides. This study recommends that journalists should be equipped with critical thinking skills and ethical considerations when navigating social media, and foolproof strategies should be put in place to sift out fake news while mitigating against citizen journalism.